A preparation process of metal modified battery
Through ultrasonic impregnation treatment and regulation liquid modification process, the cycle stability and high temperature resistance of metal-modified batteries are solved, and the Coulomb efficiency and high temperature resistance are significantly improved.
Patent Information
- Application Number
- CN202410494798.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-24
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-04-24
AI Technical Summary
The existing metal-modified batteries have deteriorated efficiency under multiple cycle conditions, and their high temperature resistance is insufficient, which limits the efficiency of the product.
The metal lithium sheet is treated with ultrasonic impregnation, and a coating layer is formed by a conditioning liquid and a modifier, and a metal-modified battery is formed by combining the electrolyte solution and the positive electrode active material. The bentonite in the regulation liquid is heat treated and cooled to optimize the spacing and activity of the sheets.
It significantly improves the Coulomb efficiency stability of the battery under multiple cycle conditions and significantly improves the product's high temperature resistance stability.
Smart Images

Figure BDA0004806613400000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, and in particular to a preparation process of a metal-modified battery. Background Art
[0002] With the development of human society, people's demand for energy is increasing. Due to the non-renewable and environmentally polluting nature of natural energy, scientists have turned their attention to battery energy. Lithium as a negative electrode material has advantages that other materials cannot match. The density of metallic lithium is very small, only 0.534g / cm3. Moreover, the gram capacity of metallic lithium is as high as 3860mAh / g, which is ten times that of graphite negative electrode (372mAh / g). Using metallic lithium as a negative electrode can reduce the amount of negative electrode material and thus increase the battery energy density. The existing metal-modified batteries have poor cycle stability, and the coulomb efficiency deteriorates under multiple cycle conditions. At the same time, the product has poor high temperature stability, which further limits the product's efficiency. Summary of the invention
[0003] In view of the defects of the prior art, the purpose of the present invention is to provide a preparation process of a metal-modified battery to solve the problems raised in the above background technology.
[0004] The present invention solves the technical problem by adopting the following technical solution:
[0005] The present invention provides a preparation process of a metal-modified battery, comprising the following steps:
[0006] Step 1, immersing the metal lithium sheet in a sufficient amount of regulating solution for ultrasonic immersion treatment, drying and setting aside after the treatment, to obtain an impregnated lithium sheet;
[0007] Step 2, coating the impregnated lithium sheet with a modifier to form a coating layer to obtain a modified negative electrode;
[0008] Step 3, dimethyl carbonate and LiPF6 are mixed in a weight ratio of 5:3 to form an electrolyte, and then aluminum foil and LiCoO2 are used as positive electrode active materials to form a positive electrode;
[0009] Step 4: Finally, the metal-modified battery is formed by modifying the negative electrode and the separator.
[0010] Preferably, the ultrasonic immersion treatment has an ultrasonic power of 350-400 W, an ultrasonic time of 20-30 min, and an ultrasonic power of 50°C.
[0011] Preferably, the preparation method of the regulating solution is:
[0012] S01: Stir and mix the bentonite in a sufficient amount of 2% hydrochloric acid solution, then wash and dry, heat treat the dried bentonite at 210-230°C for 15-20min, then cool to 155-165°C at a rate of 1-3°C / min, keep warm for 5-10min, and finally cool to 50°C at a rate of 2-5°C / min;
[0013] S02: 3-5 parts of bentonite in S01, 1-3 parts of yttrium nitrate solution, 4-7 parts of sodium lignin sulfonate solution, and 1-3 parts of silane coupling agent KH560 are mixed and stirred, and after the mixing is completed, the mixture is washed with water and dried to obtain a bentonite agent;
[0014] S03: 5-9 parts of bentonite, 8-12 parts of 1-propylsulfonic acid-3-methylimidazolium tetrafluoroborate, and 1-3 parts of glycolic acid are stirred and mixed thoroughly to obtain a regulating solution.
[0015] Preferably, the mass fraction of the yttrium nitrate solution is 4-7%.
[0016] Preferably, the mass fraction of the sodium lignin sulfonate solution is 10-15%.
[0017] Preferably, the rotation speed of the blending and stirring process is 450-550 r / min, the stirring time is 20-30 min, and the stirring temperature is 45-50°C.
[0018] Preferably, the preparation method of the modifier is:
[0019] S11: stirring and modifying the graphene and the modified liquid in a weight ratio of 2:5, washing with water and drying after the stirring is completed to obtain a graphene agent;
[0020] The preparation method of the modified liquid is as follows: 3-5 parts of lanthanum chloride solution and 1-3 parts of sodium dodecylbenzene sulfonate are added to 4-7 parts of sodium citrate solution and stirred sufficiently, and finally 1-2 parts of dodecylphenol and 0.25-0.35 parts of nano silicon dioxide are added and stirred sufficiently to obtain the modified liquid;
[0021] The polyvinyl fluoride is dissolved in 3-5 times of toluene solvent, and then a graphene agent of 5-10% of the total amount of the polyvinyl fluoride is added to the polyvinyl fluoride, and the mixture is stirred sufficiently to obtain a modifier.
[0022] Preferably, the stirring temperature of the stirring modification treatment is 48-52° C., the stirring time is 30-40 min, and the stirring speed is 550-650 r / min.
[0023] Preferably, the mass fraction of the lanthanum chloride solution is 3-5%; the mass fraction of the sodium citrate solution is 10-15%.
[0024] Preferably, the coating layer has a thickness of 1 um.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The metal modified battery of the present invention adopts a metal lithium sheet to be impregnated with a regulating solution, and then a coating modifier is used to form a coating layer, and then an electrolyte is used, and then aluminum foil and LiCoO2 are used as positive electrode active materials to form a positive electrode, and finally a metal modified battery is formed by modifying a negative electrode and a diaphragm, and the bentonite in the regulating solution is heat treated at 210-230°C for 15-20min, and then cooled to 155-165°C at a rate of 1-3°C / min, kept warm for 5-10min, and finally cooled to 50°C at a rate of 2-5°C / min, and the interlayer spacing of the bentonite is optimized, and at the same time The activity of the sheet is improved at the same time. The yttrium nitrate solution, sodium lignin sulfonate solution and silane coupling agent KH560 are mutually blended and prepared together to obtain a regulating solution that optimizes the stability of the metal lithium sheet in the system. At the same time, the modifier is coated to achieve synergistic effects, so that the coulomb efficiency stability of the obtained battery is excellent under the conditions of multiple cycles, and the product has significant high temperature stability effect; and the modifying solution blended between lanthanum chloride solution, sodium dodecylbenzene sulfonate, sodium citrate solution, dodecylphenol and nano-silica modifies graphene, and then the synergistic effect of the immersion treatment with the regulating solution in the system is further enhanced. DETAILED DESCRIPTION
[0027] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] A preparation process of a metal-modified battery of this embodiment includes the following steps:
[0029] Step 1, immersing the metal lithium sheet in a sufficient amount of regulating solution for ultrasonic immersion treatment, drying and setting aside after the treatment, to obtain an impregnated lithium sheet;
[0030] Step 2, coating the impregnated lithium sheet with a modifier to form a coating layer to obtain a modified negative electrode;
[0031] Step 3, dimethyl carbonate and LiPF6 are mixed in a weight ratio of 5:3 to form an electrolyte, and then aluminum foil and LiCoO2 are used as positive electrode active materials to form a positive electrode;
[0032] Step 4: Finally, the metal-modified battery is formed by modifying the negative electrode and the separator.
[0033] The ultrasonic immersion treatment in this embodiment has an ultrasonic power of 350-400 W, an ultrasonic time of 20-30 min, and an ultrasonic power of 50° C.
[0034] The preparation method of the regulating solution of this embodiment is:
[0035] S01: Stir and mix the bentonite in a sufficient amount of 2% hydrochloric acid solution, then wash and dry, heat treat the dried bentonite at 210-230°C for 15-20min, then cool to 155-165°C at a rate of 1-3°C / min, keep warm for 5-10min, and finally cool to 50°C at a rate of 2-5°C / min;
[0036] S02: 3-5 parts of bentonite in S01, 1-3 parts of yttrium nitrate solution, 4-7 parts of sodium lignin sulfonate solution, and 1-3 parts of silane coupling agent KH560 are mixed and stirred, and after the mixing is completed, the mixture is washed with water and dried to obtain a bentonite agent;
[0037] S03: 5-9 parts of bentonite, 8-12 parts of 1-propylsulfonic acid-3-methylimidazolium tetrafluoroborate, and 1-3 parts of glycolic acid are stirred and mixed thoroughly to obtain a regulating solution.
[0038] The mass fraction of the yttrium nitrate solution in this embodiment is 4-7%.
[0039] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 10-15%.
[0040] The rotation speed of the blending and stirring process in this embodiment is 450-550r / min, the stirring time is 20-30min, and the stirring temperature is 45-50°C.
[0041] The preparation method of the modifier of this embodiment:
[0042] S11: stirring and modifying the graphene and the modified liquid in a weight ratio of 2:5, washing with water and drying after the stirring is completed to obtain a graphene agent;
[0043] The preparation method of the modified liquid is as follows: 3-5 parts of lanthanum chloride solution and 1-3 parts of sodium dodecylbenzene sulfonate are added to 4-7 parts of sodium citrate solution and stirred sufficiently, and finally 1-2 parts of dodecylphenol and 0.25-0.35 parts of nano silicon dioxide are added and stirred sufficiently to obtain the modified liquid;
[0044] The polyvinyl fluoride is dissolved in 3-5 times of toluene solvent, and then a graphene agent of 5-10% of the total amount of the polyvinyl fluoride is added to the polyvinyl fluoride, and the mixture is stirred sufficiently to obtain a modifier.
[0045] The stirring temperature of the stirring modification treatment in this embodiment is 48-52° C., the stirring time is 30-40 min, and the stirring speed is 550-650 r / min.
[0046] The mass fraction of the lanthanum chloride solution in this embodiment is 3-5%; the mass fraction of the sodium citrate solution is 10-15%.
[0047] The coating layer thickness of this embodiment is 1 um.
[0048] Example 1.
[0049] A preparation process of a metal-modified battery of this embodiment includes the following steps:
[0050] Step 1, immersing the metal lithium sheet in a sufficient amount of regulating solution for ultrasonic immersion treatment, drying and setting aside after the treatment, to obtain an impregnated lithium sheet;
[0051] Step 2, coating the impregnated lithium sheet with a modifier to form a coating layer to obtain a modified negative electrode;
[0052] Step 3, dimethyl carbonate and LiPF6 are mixed in a weight ratio of 5:3 to form an electrolyte, and then aluminum foil and LiCoO2 are used as positive electrode active materials to form a positive electrode;
[0053] Step 4: Finally, the metal-modified battery is formed by modifying the negative electrode and the separator.
[0054] The ultrasonic power of the ultrasonic immersion treatment in this embodiment is 350W, the ultrasonic time is 20min, and the ultrasonic power is 50°C.
[0055] The preparation method of the regulating solution of this embodiment is:
[0056] S01: The bentonite is first stirred and mixed in a sufficient amount of 2% hydrochloric acid solution, then washed with water and dried, the dried bentonite is first heat treated at 210°C for 15 minutes, then cooled to 155°C at a rate of 1°C / min, kept warm for 5 minutes, and finally cooled to 50°C at a rate of 2°C / min;
[0057] S02: 3 parts of bentonite in S01, 1 part of yttrium nitrate solution, 4 parts of sodium lignin sulfonate solution and 1 part of silane coupling agent KH560 are mixed and stirred, and after the mixing is completed, the mixture is washed with water and dried to obtain a bentonite agent;
[0058] S03: 5 parts of bentonite, 8 parts of 1-propylsulfonic acid-3-methylimidazolium tetrafluoroborate and 1 part of glycolic acid were stirred and mixed thoroughly to obtain a regulating solution.
[0059] The mass fraction of the yttrium nitrate solution in this embodiment is 4%.
[0060] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 10%.
[0061] The rotation speed of the blending and stirring process in this embodiment is 450 r / min, the stirring time is 20 min, and the stirring temperature is 45°C.
[0062] The preparation method of the modifier of this embodiment:
[0063] S11: stirring and modifying the graphene and the modified liquid in a weight ratio of 2:5, washing with water and drying after the stirring is completed to obtain a graphene agent;
[0064] The preparation method of the modified liquid is as follows: 3 parts of lanthanum chloride solution and 1 part of sodium dodecylbenzene sulfonate are added to 4 parts of sodium citrate solution and stirred sufficiently, and finally 1 part of dodecylphenol and 0.25 parts of nano silicon dioxide are added and stirred sufficiently to obtain the modified liquid;
[0065] The polyvinyl fluoride was dissolved in 3 times of toluene solvent, and then a graphene agent of 5% of the total amount of the polyvinyl fluoride was added to the polyvinyl fluoride, and the mixture was stirred sufficiently to obtain a modifier.
[0066] The stirring temperature of the stirring modification treatment in this embodiment is 48° C., the stirring time is 30 min, and the stirring speed is 550 r / min.
[0067] The mass fraction of the lanthanum chloride solution in this embodiment is 3%; the mass fraction of the sodium citrate solution is 10%.
[0068] The coating layer thickness of this embodiment is 1 um.
[0069] Example 2.
[0070] A preparation process of a metal-modified battery of this embodiment includes the following steps:
[0071] Step 1, immersing the metal lithium sheet in a sufficient amount of regulating solution for ultrasonic immersion treatment, drying and setting aside after the treatment, to obtain an impregnated lithium sheet;
[0072] Step 2, coating the impregnated lithium sheet with a modifier to form a coating layer to obtain a modified negative electrode;
[0073] Step 3, dimethyl carbonate and LiPF6 are mixed in a weight ratio of 5:3 to form an electrolyte, and then aluminum foil and LiCoO2 are used as positive electrode active materials to form a positive electrode;
[0074] Step 4: Finally, the metal-modified battery is formed by modifying the negative electrode and the separator.
[0075] The ultrasonic power of the ultrasonic immersion treatment in this embodiment is 400 W, the ultrasonic time is 30 min, and the ultrasonic power is 50°C.
[0076] The preparation method of the regulating solution of this embodiment is:
[0077] S01: The bentonite is first stirred and mixed in a sufficient amount of 2% hydrochloric acid solution, then washed with water and dried, the dried bentonite is first heat treated at 230°C for 20 minutes, then cooled to 165°C at a rate of 3°C / min, kept warm for 10 minutes, and finally cooled to 50°C at a rate of 5°C / min;
[0078] S02: 5 parts of bentonite in S01, 3 parts of yttrium nitrate solution, 7 parts of sodium lignin sulfonate solution and 3 parts of silane coupling agent KH560 are mixed and stirred, and after the mixing is completed, the mixture is washed with water and dried to obtain a bentonite agent;
[0079] S03: 9 parts of bentonite, 12 parts of 1-propylsulfonic acid-3-methylimidazolium tetrafluoroborate and 3 parts of glycolic acid were stirred and mixed thoroughly to obtain a regulating solution.
[0080] The mass fraction of the yttrium nitrate solution in this embodiment is 7%.
[0081] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 15%.
[0082] The rotation speed of the blending and stirring process in this embodiment is 550 r / min, the stirring time is 30 min, and the stirring temperature is 50°C.
[0083] The preparation method of the modifier of this embodiment:
[0084] S11: stirring and modifying the graphene and the modified liquid in a weight ratio of 2:5, washing with water and drying after the stirring is completed to obtain a graphene agent;
[0085] The preparation method of the modified liquid is as follows: 5 parts of lanthanum chloride solution and 3 parts of sodium dodecylbenzene sulfonate are added to 7 parts of sodium citrate solution and stirred sufficiently, and finally 2 parts of dodecylphenol and 0.35 parts of nano silicon dioxide are added and stirred sufficiently to obtain the modified liquid;
[0086] The polyvinyl fluoride was dissolved in 5 times toluene solvent, and then a graphene agent of 10% of the total amount of the polyvinyl fluoride was added to the polyvinyl fluoride, and the mixture was stirred sufficiently to obtain a modifier.
[0087] The stirring temperature of the stirring modification treatment in this embodiment is 52° C., the stirring time is 40 min, and the stirring speed is 650 r / min.
[0088] The mass fraction of the lanthanum chloride solution in this embodiment is 5%; the mass fraction of the sodium citrate solution is 15%.
[0089] The coating layer thickness of this embodiment is 1 um.
[0090] Example 3.
[0091] A preparation process of a metal-modified battery of this embodiment includes the following steps:
[0092] Step 1, immersing the metal lithium sheet in a sufficient amount of regulating solution for ultrasonic immersion treatment, drying and setting aside after the treatment, to obtain an impregnated lithium sheet;
[0093] Step 2, coating the impregnated lithium sheet with a modifier to form a coating layer to obtain a modified negative electrode;
[0094] Step 3, dimethyl carbonate and LiPF6 are mixed in a weight ratio of 5:3 to form an electrolyte, and then aluminum foil and LiCoO2 are used as positive electrode active materials to form a positive electrode;
[0095] Step 4: Finally, the metal-modified battery is formed by modifying the negative electrode and the separator.
[0096] The ultrasonic power of the ultrasonic immersion treatment in this embodiment is 370W, the ultrasonic time is 25min, and the ultrasonic power is 50°C.
[0097] The preparation method of the regulating solution of this embodiment is:
[0098] S01: The bentonite is first stirred and mixed in a sufficient amount of 2% hydrochloric acid solution, then washed with water and dried, the dried bentonite is first heat treated at 220°C for 17 minutes, then cooled to 160°C at a rate of 2°C / min, kept warm for 7.5 minutes, and finally cooled to 50°C at a rate of 3.5°C / min;
[0099] S02: 4 parts of bentonite in S01, 2 parts of yttrium nitrate solution, 5.5 parts of sodium lignin sulfonate solution and 2 parts of silane coupling agent KH560 are mixed and stirred, and after the mixing is completed, the mixture is washed with water and dried to obtain a bentonite agent;
[0100] S03: 7 parts of bentonite, 10 parts of 1-propylsulfonic acid-3-methylimidazolium tetrafluoroborate and 2 parts of glycolic acid were stirred and mixed thoroughly to obtain a regulating solution.
[0101] The mass fraction of the yttrium nitrate solution in this embodiment is 5.5%.
[0102] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 12.5%.
[0103] The rotation speed of the blending and stirring process in this embodiment is 500 r / min, the stirring time is 25 min, and the stirring temperature is 47°C.
[0104] The preparation method of the modifier of this embodiment:
[0105] S11: stirring and modifying the graphene and the modified liquid in a weight ratio of 2:5, washing with water and drying after the stirring is completed to obtain a graphene agent;
[0106] The preparation method of the modified liquid is as follows: 4 parts of lanthanum chloride solution and 2 parts of sodium dodecylbenzene sulfonate are added to 5.5 parts of sodium citrate solution and stirred sufficiently, and finally 1.5 parts of dodecylphenol and 0.30 parts of nano silicon dioxide are added and stirred sufficiently to obtain the modified liquid;
[0107] The polyvinyl fluoride was dissolved in 4 times toluene solvent, and then a graphene agent of 7.5% of the total amount of the polyvinyl fluoride was added to the polyvinyl fluoride, and the mixture was stirred sufficiently to obtain a modifier.
[0108] The stirring temperature of the stirring modification treatment in this embodiment is 50° C., the stirring time is 35 min, and the stirring speed is 600 r / min.
[0109] The mass fraction of the lanthanum chloride solution in this embodiment is 4%; the mass fraction of the sodium citrate solution is 12.5%.
[0110] The coating layer thickness of this embodiment is 1 um.
[0111] Example 4.
[0112] A preparation process of a metal-modified battery of this embodiment includes the following steps:
[0113] Step 1, immersing the metal lithium sheet in a sufficient amount of regulating solution for ultrasonic immersion treatment, drying and setting aside after the treatment, to obtain an impregnated lithium sheet;
[0114] Step 2, coating the impregnated lithium sheet with a modifier to form a coating layer to obtain a modified negative electrode;
[0115] Step 3, dimethyl carbonate and LiPF6 are mixed in a weight ratio of 5:3 to form an electrolyte, and then aluminum foil and LiCoO2 are used as positive electrode active materials to form a positive electrode;
[0116] Step 4: Finally, the metal-modified battery is formed by modifying the negative electrode and the separator.
[0117] The ultrasonic power of the ultrasonic immersion treatment in this embodiment is 360W, the ultrasonic time is 22min, and the ultrasonic power is 50°C.
[0118] The preparation method of the regulating solution of this embodiment is:
[0119] S01: The bentonite is first stirred and mixed in a sufficient amount of 2% hydrochloric acid solution, then washed with water and dried, the dried bentonite is first heat treated at 212°C for 16 minutes, then cooled to 157°C at a rate of 2°C / min, kept warm for 6 minutes, and finally cooled to 50°C at a rate of 3°C / min;
[0120] S02: 4 parts of bentonite in S01, 2 parts of yttrium nitrate solution, 5 parts of sodium lignin sulfonate solution and 2 parts of silane coupling agent KH560 are mixed and stirred, and after the mixing is completed, the mixture is washed with water and dried to obtain a bentonite agent;
[0121] S03: 6 parts of bentonite, 9 parts of 1-propylsulfonic acid-3-methylimidazolium tetrafluoroborate and 2 parts of glycolic acid were stirred and mixed thoroughly to obtain a regulating solution.
[0122] The mass fraction of the yttrium nitrate solution in this embodiment is 5%.
[0123] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 12%.
[0124] The rotation speed of the blending and stirring process in this embodiment is 460 r / min, the stirring time is 22 min, and the stirring temperature is 46°C.
[0125] The preparation method of the modifier of this embodiment:
[0126] S11: stirring and modifying the graphene and the modified liquid in a weight ratio of 2:5, washing with water and drying after the stirring is completed to obtain a graphene agent;
[0127] The preparation method of the modified liquid is as follows: 4 parts of lanthanum chloride solution and 2 parts of sodium dodecylbenzene sulfonate are added to 5 parts of sodium citrate solution and stirred sufficiently, and finally 1.2 parts of dodecylphenol and 0.27 parts of nano silicon dioxide are added and stirred sufficiently to obtain the modified liquid;
[0128] The polyvinyl fluoride was dissolved in 4 times of toluene solvent, and then a graphene agent of 6% of the total amount of the polyvinyl fluoride was added to the polyvinyl fluoride, and the mixture was stirred sufficiently to obtain a modifier.
[0129] The stirring temperature of the stirring modification treatment in this embodiment is 49° C., the stirring time is 32 min, and the stirring speed is 560 r / min.
[0130] The mass fraction of the lanthanum chloride solution in this embodiment is 4%; the mass fraction of the sodium citrate solution is 12%.
[0131] The coating layer thickness of this embodiment is 1 um.
[0132] Comparative Example 1.
[0133] The difference from Example 3 is that no conditioning solution treatment was used.
[0134] Comparative Example 2.
[0135] The difference from Example 3 is that bentonite containing S01 is not added to the conditioning solution.
[0136] Comparative Example 3.
[0137] The difference from Example 3 is that no yttrium nitrate solution and silane coupling agent KH560 are added to the regulating solution.
[0138] Comparative Example 4.
[0139] The difference from Example 3 is that no modifier treatment was used.
[0140] Comparative Example 5.
[0141] The difference from Example 3 is that the modifier is not treated with a modifying liquid.
[0142] The coulombic efficiency of Examples 1-4 and Comparative Examples 1-5 was tested by 100 cycles of performance cycles. The coulombic temperature stability of the products at 50, 60 and 70°C was measured. The results are as follows:
[0143]
[0144] From Examples 1-4 and Comparative Examples 1-5, it can be concluded that the product of Example 3 of the present invention has a significant effect on the stability of coulombic efficiency at 50, 60 and 70°C for 100 times, and the product stability still has a significant effect after a change of 50-70°C;
[0145] The present invention does not use regulating liquid treatment and modifier treatment, and the effect of coulomb efficiency temperature stability is obviously deteriorated. The two are coordinated and synergistic, and the performance effect of the product is most obvious. At the same time, bentonite without S01 is added to the regulating liquid, yttrium nitrate solution and silane coupling agent KH560 are not added to the regulating liquid, and the modifier is not treated with modifying liquid. The performance of the product shows a trend of deterioration. Based on this, the preparation method of the present invention is used to obtain the regulating liquid and modifier treatment, and the performance effect of the product is the most significant. Using other methods instead is not as obvious as the effect of the present invention.
[0146] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0147] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A process for preparing a metal-modified battery, characterized in that: The following steps are involved: Step 1, immersing the metal lithium sheet in a sufficient amount of regulating solution for ultrasonic immersion treatment, drying and setting aside after the treatment, to obtain an impregnated lithium sheet; Step 2, coating the impregnated lithium sheet with a modifier to form a coating layer to obtain a modified negative electrode; Step 3, dimethyl carbonate and LiPF6 are mixed in a weight ratio of 5:3 to form an electrolyte, and then aluminum foil and LiCoO2 are used as positive electrode active materials to form a positive electrode; Step 4, finally, a metal-modified battery is formed by modifying the negative electrode and the separator; The preparation method of the regulating solution is: S01: Stir and mix the bentonite in a sufficient amount of 2% hydrochloric acid solution, then wash and dry, heat treat the dried bentonite at 210-230°C for 15-20min, then cool to 155-165°C at a rate of 1-3°C / min, keep warm for 5-10min, and finally cool to 50°C at a rate of 2-5°C / min; S02: 3-5 parts of bentonite in S01, 1-3 parts of yttrium nitrate solution, 4-7 parts of sodium lignin sulfonate solution, and 1-3 parts of silane coupling agent KH560 are mixed and stirred, and after the mixing is completed, the mixture is washed with water and dried to obtain a bentonite agent; S03: 5-9 parts of bentonite, 8-12 parts of 1-propylsulfonic acid-3-methylimidazolium tetrafluoroborate, and 1-3 parts of glycolic acid are stirred and mixed to obtain a regulating solution; The preparation method of the modifier: S11: stirring and modifying the graphene and the modified liquid in a weight ratio of 2:5, washing with water and drying after the stirring is completed to obtain a graphene agent; The preparation method of the modified liquid is as follows: 3-5 parts of lanthanum chloride solution and 1-3 parts of sodium dodecylbenzene sulfonate are added to 4-7 parts of sodium citrate solution and stirred sufficiently, and finally 1-2 parts of dodecylphenol and 0.25-0.35 parts of nano silicon dioxide are added and stirred sufficiently to obtain the modified liquid; The polyvinyl fluoride is dissolved in 3-5 times of toluene solvent, and then 5-10% of the total amount of the polyvinyl fluoride graphene agent is added to the polyvinyl fluoride, and the mixture is stirred sufficiently to obtain a modifier.
2. A process for preparing a metal-modified battery according to claim 1, characterized in that: The ultrasonic immersion treatment has an ultrasonic power of 350-400W, an ultrasonic time of 20-30min, and an ultrasonic power of 50°C.
3. The preparation process of a metal-modified battery according to claim 1, characterized in that: The mass fraction of the yttrium nitrate solution is 4-7%.
4. The process for preparing a metal-modified battery according to claim 3, characterized in that: The mass fraction of the sodium lignin sulfonate solution is 10-15%.
5. The process for preparing a metal-modified battery according to claim 3, characterized in that: The rotation speed of the blending and stirring process is 450-550r / min, the stirring time is 20-30min, and the stirring temperature is 45-50°C.
6. The process for preparing a metal-modified battery according to claim 5, characterized in that: The stirring temperature of the stirring modification treatment is 48-52° C., the stirring time is 30-40 min, and the stirring speed is 550-650 r / min.
7. The process for preparing a metal-modified battery according to claim 6, characterized in that: The mass fraction of the lanthanum chloride solution is 3-5%; the mass fraction of the sodium citrate solution is 10-15%.
8. The process for preparing a metal-modified battery according to claim 1, characterized in that: The coating layer has a thickness of 1 um.
Citation Information
Patent Citations
Metal lithium anode with protective coating, preparation thereof and application of metal lithium anode
CN106159200A